Desain PI Controller menggunakan Ziegler Nichols Tuning pada Proses Nonlinier Multivariabel - Poppy Dewi Lestari; Abdul Hadi (UIN Sultan Syarif Kasim Riau, 2012)
Control on chemical process industries are generally nonlinear time variant, so that it needs a good performance. Controller Design is a series of how to get started with system control mathematical model system tuning parameters are controlled, controllers and simulate the design results. The controller has a good performance is obtained by providing accurate controller tuning parameters. This research discusses the design of PI controller using the Tuning in process Ziegeler Nichols Nonlinear Multivariable.The system is controlled using Matlab-Simulink simulated so get a response-controlled system. Response system that is used to determine the parameters of the method Ziegler Nichols.The result shows, PI controller design using Ziegler Nichols Tuning can reduce the time duration of tuning parameter control. By using the control Parameter Tuning for control of Ziegler Nichols open loop (method of reaction curves) on the output flow rate F (t) and the concentration of c-output (t) obtained the value of Kp = 0.36 and Ki = 1.666 .7 as for controlling close loop (oscillation method) on the output flow rate F (t) obtained the value of Kp = 0.45 and Ki = 0.69 and concentration of c-output (t) value = 0.45 Kp and Ki = ▲ 0.935.Keywords : PI Controller, Ziegler Nichols Tuning, Nonlinear Multivariable